An epidemiological study of androgenic alopecia in 3114 Korean patients. (January 2014) - Yeo, I. K.; Jang, W. S.; Min, P. K.; Cho, H. R.; Cho, S. W.; Hong, N. S.; Kang, J. S.; Ki, D. H.; Kim, H. J.; Kim, Y. C.; Kim, Y. S.; Lee, I. J.; et al.
Summary Background Androgenetic alopecia (AGA) is the most common type of hair loss, and is characterized by the transformation of terminal scalp hair into vellus hair. The epidemiology of AGA is not fully understood. A strong genetic basis has long been identified, although little is known of its nongenetic causes. Aim To evaluate the association of AGA with a number of environmental factors, including smoking, drinking and sleeping habit. Methods In total, 3114 Korean individuals with AGA who attended any one of 17 dermatology clinics in 6 cities in South Korea between March 2011 and February 2012 were enrolled in the study. Epidemiologic a data were collected using a standard questionnaire. Results No association was seen between eating or sleeping habits and severity of hair loss. However, drinking and smoking were associated with the severity of AGA in male patients. We also found that patients of both genders with a family history had more advanced types of hair loss, and the age of onset of AGA in male patients with a family history was earlier than that in male patients without a family history. Conclusions Although the evidence for an environmental influence on AGA remains very weak, we did find an association between hair loss severity and certain environmental factors, such as smoking and drinking. Family history with more severe hair loss and an earlier age of onset.